Popular journalism in China: A study of China Youth Daily. (September 2018) - Wang, Haiyan; Sparks, Colin; Yu, Huang
It is commonly stated that the press in China can be divided into two main categories, the party-oriented official press and the market-oriented commercial press. This article examines an official paper, China Youth Daily, which is a central organ of the Communist Youth League of China. The findings of a content analysis demonstrate that this title differs significantly from other central official titles, like People's Daily, but also from commercial papers, like Southern Metropoli s Daily . While China Youth Daily's journalism is close to the official pole in the amount of propaganda-related material it covers, it also has a greater emphasis on watchdog journalism than does People's Daily . It places a much greater emphasis on infotainment than do either of the official and commercial poles. It is more likely to use journalistic techniques like sensationalism and the revelation of personal details than are the other titles analysed. These findings lead to the conclusion that the bi-polar characterization of the Chinese press requires modification. At least one prominent national title is best described as 'popular official' media. One of the main features of this kind of journalism is that it presents the party and business elite in a human light and thus constitutes a renewal of the repertoire of hegemonic devices at the party's disposal. What is certainly the case is that the frequent claim that there is a contradiction between popular journalism responding to audience tastes and official journalism constrained by the propaganda needs of the party is mistaken.